Schwannoma in the nasal cavity: A benign nerve sheath tumor at an odd location (Indian Journal of Case Reports, 2024)
Schwannomas are neurogenic tumors arising from the Schwann cells present in the neural sheath of the myelinated nerves. These are benign tumors that can arise anywhere in the body. Schwannomas are rarely seen in the nose and paranasal sinuses representing <4% of all head-and-neck schwannomas. Surgical excision is the treatment of choice in these cases. Nasal polyps are common nasal cavity lesions which are usually inflammatory polyps. Schwannoma of the nasal cavity usually presented with headache, unilateral nasal obstruction due to mass obliterating the nasal cavity, and epistaxis. Here, we report the case of a 47-year-old female who presented with a mass in the left nasal cavity causing the nasal blockage.